Case Report: Synergistic central nervous system depression of baclofen and pregabalin: clinical pharmacist-driven case analysis and case review - Xie, Yitong; Wu, Danwei; Jin, Peihao; Mao, Lu; Zhen, Jiancun; Zhang, Wei (Frontiers in Pharmacology, 2025)
BackgroundBaclofen, a γ-aminobutyric acid (GABA) derivative, and Pregabalin, a GABA analogue, are widely prescribed for muscle spasm and neuropathic pain. This first-reported case demonstrates synergistic central nervous system (CNS) depression of Baclofen (30 mg/day) and Pregabalin (300 mg/day) in a patient with mild renal impairment [estimated glomerular filtration rate, (eGFR) = 77.26 mL/min].Case PresentationA 68-year-old female with renal impairment developed progressive CNS depression (somnolence, coma) following combined Baclofen (30 mg/day) and Pregabalin (300 mg/day) therapy after spinal fusion surgery. CNS depression was completely resolved 48 h after drug discontinuation.ConclusionClinicians should exercise heightened caution when combining Baclofen and Pregabalin in renal impairment. Dose adjustments based on creatinine clearance (CLcr) are strongly recommended. Particular attention should be given to initiating therapy with reduced starting doses in patients at elevated risk of CNS depression.